2012
DOI: 10.1177/0018720812451855
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Rhythms as a Basis for Work Organization

Abstract: The findings can be applied in any work design, but they are especially suited for highly demanding work carried out outdoors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 21 publications
(22 reference statements)
0
8
0
Order By: Relevance
“…We identified one cluster randomized controlled trial reported in two articles [ 72 , 73 ], one controlled before- and after study [ 74 ] and two uncontrolled before- and after studies [ 75 , 76 ] ( Table 2 ). Anger at al.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We identified one cluster randomized controlled trial reported in two articles [ 72 , 73 ], one controlled before- and after study [ 74 ] and two uncontrolled before- and after studies [ 75 , 76 ] ( Table 2 ). Anger at al.…”
Section: Resultsmentioning
confidence: 99%
“…[ 75 ] presented a pilot study in preparation of a larger RCT. One study targeted the intervention (training to improve the psychosocial work environment) at supervisors only, with measurement of the changes in health outcomes in their subordinates [ 74 ], one study targeted the intervention at supervisors and shop-floor workers [ 75 ], and the remaining two studies targeted shop-floor workers only [ 72 , 73 , 76 ]. Total sample size across the four studies was 260 from a variety of occupations within construction.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations